Dinamika Biaya Politik yang Tinggi dalam Politik dan Dampaknya terhadap Korupsi yang Berkelanjutan - Dharayanti, Desak Made Pratiwi; Smrti, Ni Nyoman Emang; Sukenada, I Putu Gede (Postgraduate Program in Law, Pattimura University, 2024)
Introduction: In Indonesia there are no rules governing political costs for campaigns, in this study the focus is on the large costs of the campaign whether it is the cause of corruption in Indonesia.Purposes of the Research: This paper aims to analyze the connectivity of politics with corruption as the cause of people's suffering and high-cost politics as the root of corruption.Methods of the Research: The research method used in this paper is normative legal research method. Conceptual approach and statutory approach are used in this research. Legal materials are identified through document studies. The analytical approach applied is qualitative.Results Originality of the Research: indicate that these high political costs force winners to find ways to return their investment, which often involves corrupt practices. In addition, corruption is also linked to vote-buying practices involving voters in elections. This practice is linked to patronage and clientelism, where voters receive material rewards in the form of money or goods to support a particular candidate. Overall, corruption and high-cost politics have undermined the democratic process in Indonesia and affected the integrity of the political system. Corruption is not only a legal issue, but also a complex cultural and political issue.